1990
DOI: 10.1051/geotech/1990052011
|View full text |Cite
|
Sign up to set email alerts
|

Spécification des charges et des écoulements dans les silos métalliques

Abstract: RésuméCet article présente une partie des travaux effectués dans le cadre de la « Mis sion Silos » en collaboration avec le CTICM.Deux aspects nous ont intéressés : d'abord l'analyse des différents types d'écou lement durant la vidange caractérisés par la détermination des profils de vitesse sur modèle réduit ; ensuite l'interprétation des résultats des mesures expérimen tales des efforts en paroi comparés aux méthodes de calculs de WALTERS, SOKOL et à la norme DIN.Cette analyse comparative démontre que les mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…However, these authors did report that horizontal overpressures in the order of two have been observed for silos which exhibit an effective transition (e.g. Khelil, 1989;Khelil and Roth, 1990). It will be shown in what follows that the discharge overpressure predictions of the mixed flow theory are commensurate with observations from these and other past experiments (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, these authors did report that horizontal overpressures in the order of two have been observed for silos which exhibit an effective transition (e.g. Khelil, 1989;Khelil and Roth, 1990). It will be shown in what follows that the discharge overpressure predictions of the mixed flow theory are commensurate with observations from these and other past experiments (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to Newtonian fluids, these two orthogonal stresses are not equal, and they are linked by a Janssen coefficient defined in the present work as k j [ 1,2 ] : kj=σhσv These two normal stresses are presented in Mohr's circle; the vertical stress is presented as a major principal stress, and the small stress (horizontal stress) is a minor principal stress. Thus, k j is the ratio of the major and minor principal stresses; its value can be measured using shear testers (eg, an FT4 powder rheometer) as a function of internal angle friction as follows [ 3,4 ] : truekj=1sinδ1+sinδ The analysis of the principal stresses inside cylindrical and conical hoppers is based on the Janssen model applied to the static or dynamic states of the granular system inside cylindrical hoppers. This model indicates that, for a shallow powder bed, the normal stresses are quasi‐equivalent to the static pressure of fluids, which is a linear function of powder depth.…”
Section: Introductionmentioning
confidence: 99%
“…However, these authors did report that horizontal overpressures in the order of two have been observed for silos which exhibit an effective transition (e.g. Khelil, 1989;Khelil and Roth, 1990). It will be shown in what follows that the discharge overpressure predictions of the mixed flow theory are commensurate with observations from these and other past experiments (e.g.…”
Section: Introductionmentioning
confidence: 99%